Respuesta :
Answer:
The resulting expression is:
[tex]4\left[0.5+2.5y-0.7x-1.3+4\right]\:=-2.8x+10y+12.8[/tex]
Step-by-step explanation:
Given the expression
[tex]4\left[0.5+2.5y-0.7x-1.3+4\right]\:[/tex]
simplifying
[tex]=\left(4\right)\left(0.5+2.5y+-0.7x+-1.3+4\right)[/tex]
[tex]=\left(4\right)\left(0.5\right)+\left(4\right)\left(2.5y\right)+\left(4\right)\left(-0.7x\right)+\left(4\right)\left(-1.3\right)+\left(4\right)\left(4\right)[/tex]
[tex]=2+10y-2.8x-5.2+16[/tex]
[tex]=-2.8x+10y+12.8[/tex]
Thus, the resulting expression is:
[tex]4\left[0.5+2.5y-0.7x-1.3+4\right]\:=-2.8x+10y+12.8[/tex]
Answer:
there is no help if u dont give straight answers
give straight answers
Step-by-step explanation:
i think its A if not could be C or D